Peluang, Tantangan dan Harapan Trio Batak Perempuan di Kota Medan - Cahyani Yesika Br Silaban; Mauly Purba (Journal on Education, 2024)
The rise of modern music is growing in all circles so that the female Batak trio is never noticed and finds a place to look for job opportunities in the city of Medan. This research is a type of qualitative research by observing artistic phenomena, especially the opportunities, challenges and hopes of the Batak Women Trio in Medan City. Data collection techniques using interviews and observation. Data analysis techniques use data reduction, data presentation and drawing conclusions. This research was carried out in Medan City. Research results: 1) This female Batak trio is starting to become less popular with music listeners in the city of Medan, this is due to the many developments in modern music which are more popular for the people of Medan to listen to in the city of Medan. 2) This female Batak trio singer still has a place in the hearts of the people of Medan, but not like before, who was in demand by all groups. As a singer, he hopes that this Batak trio will get more attention, meaning this is the hope of the female Batak trio in the city of Medan. 3) The female Batak trio in the city of Medan must also be able to adapt to the challenges which have resulted in a change in the musical concept from the Batak trio to modern music so that the Batak trio is also able to compete with the existing challenges. Where the Batak trio must change their musical presentation to make it more modern so that Batak trio music lovers feel the same musical perception as their musical tastes.